Polemic and Reasons for Reusing Wayang and Gamelan as A Medium for Contemporary Preaching Islam Religion in Central Java, Indonesia - Setiawan, Aris (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
This study aims to reveal the main reasons why wayang kulit (shadow puppets) and gamelan music were used again as tools of Islamic da’wah after the Wali Sanga era (Nine Saints). In Central Java (Banyumas, Solo, Demak, Pati), there has been a phenomenon of Islamic preaching and recitation performed by Kiai using wayang kulit and gamelan music. This study uses a phenomenological approach, which is to get an explanation of the apparent reality. This approach focuses on events that are seen as having an impact, polemic, and discourse on life. This study also uses a critical approach, looking critically at the phenomenon of -art- being researched to test how far the view that puts that wayang (and gamelan) is not by religious rules is accepted, rejected, and even opposed. The result shows that although da’wah using wayang and gamelan has sparked a lot of polemics, the use of wayang and gamelan music is considered more effective in spreading Islamic teachings to grassroots communities due to two factors. First, continuing the trace of tradition brought by the first Islamic missionaries in Java (Wali Sanga). Second, to make people aware, especially young santri (prospective preachers) or congregation today, realize that Islam is spread peacefully and without resistance through art.